Correlation Between Daily Dietary Micronutrients Intake and Mental Health Outcomes in Iranians Living With HIV Infection. (November 2016) - Jamali, Faezeh; Izadi, Azimeh; Khalili, Hossein; Garmaroudi, Gholamreza
Abstract : N/A: In this study, we evaluated the correlation between daily dietary antioxidant micronutrients intake and mental health outcomes in Iranians living with HIV infection. During an organized interview, daily dietary micronutrients intake of people living with HIV (PLWH; N = 100) was evaluated using a 168‐item semi‐quantitative food frequency questionnaire. A reliable psychiatric questionnaire was used to assess depression, anxiety, and stress of the patients as mental health outcomes. Significant negative correlations were found between daily dietary intake of zinc, selenium, and vitamin C with mental health outcomes, including depression, anxiety, and stress scores in Iranian PLWH. In our study, daily dietary intake of some antioxidant micronutrients correlated with the mental health outcomes of Iranian PLWH.